2015
DOI: 10.3390/su70810809
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Building Envelope: A Novel Multi-Objective Approach for the Optimization of Energy Performance and Thermal Comfort

Abstract: According to the increasing worldwide attention to energy and the environmental performance of the building sector, building energy demand should be minimized by considering all energy uses. In this regard, the development of building components characterized by proper values of thermal transmittance, thermal capacity, and radiative properties is a key strategy to reduce the annual energy need for the microclimatic control. However, the design of the thermal characteristics of the building envelope is an arduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 38 publications
2
62
0
Order By: Relevance
“…Neglecting their presence can lead to significant underestimation of actual heat flows, which can account form 5% to almost 20% of total heat flows through the building envelope, depending mostly on the thermal transmittance of the load bearing wall and the ventilation characteristics of the air cavity. Ascione [6] found that, if the thickness of the thermal insulation layer increases, the U-value of the entire wall will not provide the optimal value in some cases that directly depend on climate conditions. In addition, the material of the bearing layer of the external wall, with its significant thermal properties, can be different from the masonry, made of monolithic concrete, which has low thermal properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neglecting their presence can lead to significant underestimation of actual heat flows, which can account form 5% to almost 20% of total heat flows through the building envelope, depending mostly on the thermal transmittance of the load bearing wall and the ventilation characteristics of the air cavity. Ascione [6] found that, if the thickness of the thermal insulation layer increases, the U-value of the entire wall will not provide the optimal value in some cases that directly depend on climate conditions. In addition, the material of the bearing layer of the external wall, with its significant thermal properties, can be different from the masonry, made of monolithic concrete, which has low thermal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Ascione [4] learned that thermal bridges can increase the heating demand of buildings by over 20%. This influence depends on weather conditions [5], level of insulation [6], the thermal bridges' construction [7][8][9], the type of building (use and geometry), and the method used to implement its effect within the calculation of the building energy demand [4]. Approaches of thermal bridges in regulation are different in the EPBD context [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal comfort ranges of inhabitants as well can have an important impact [70]. We neglected this due to our assumption that the buildings have the same initial thermal insulation state and are situated in the same climate.…”
Section: Excluded Effectsmentioning
confidence: 99%
“…Indeed, in order to provide high-efficiency new buildings, it is enough to establish prescriptions concerning minimum energy performance. Conversely, incentives and public funding may be necessary to promote energy efficiency when not mandatory, and thus in case of energy retrofit (or refurbishment) of the existing • in [7] for what concerns the adoption of standard economic indicators to a historical building; • in [8] with reference to a residential case study for what concerns the building shell retrofit; and • in [9] in matter of overall energy refurbishment of a multi-storey building for households by taking into account the building shell and all active energy systems.…”
Section: Introduction: Importance Of Large-scale Energy Retrofit Of Tmentioning
confidence: 99%